Understanding the Impact of the Canada Prenatal Nutrition Program: A Quantitative Evaluation - Muhajarine, Nazeem (Can J Public Health, 2012)
Objectives: The objectives of this study were to assess whether high exposure to the Canada Prenatal Nutrition Program (CPNP) improved 1) the personal health practices, such as smoking and breastfeeding, of participants and 2) birth outcomes, such as low birth weight and preterm birth. Intervention: The CPNP is a population-level health intervention that aims to contribute to improved health outcomes for pregnant women and their newborn children facing conditions of risk. The program, which is jointly managed by the federal and provincial governments, serves more than 45,000 Canadian women annually. Participants: Participants were women who entered the program prenatally in 2002–2006 and were socially, demographically and geographically diverse. Almost 12% were adolescents, and almost 10% were over 34 years of age; 5% were recent immigrants (in Canada <10 years), and close to one quarter were Aboriginal. Setting: This comprised a broad range of community-based projects in 2,000 communities. Outcomes: Descriptive statistics showed that the CPNP is reaching the women for which it is intended. Participants with high CPNP exposure were more likely to reduce the number of cigarettes they smoked, to cease drinking, to breastfeed their infants and to breastfeed for longer, and to increase their use of vitamin/mineral supplements from never to daily. Furthermore, they were less likely to give birth to an infant that was preterm, had low birth weight, was small for gestational age or had poor neonatal health. Unexpectedly, participants were more likely to give birth to a large-for-gestational-age infant. Our stratified “equity” analyses showed some variation by social group, indicating that the benefits were not consistently shared by all. Conclusion: High CPNP exposure improved the health behaviours and birth outcomes of women and their newborn children facing conditions of risk. Furthermore, our equity analysis found that the associations between higher CPNP exposure and healthy behaviour changes, and even more so, better birth outcomes, were generally found across many social groups. In the absence of a control group, the study used an innovative approach to estimating the impact of the CPNP by comparing those who received a higher “dose” with those receiving a lower dose of CPNP services.